Pengembangan Perangkat Pembelajaran Berbasis Model SiMaYang Tipe 2 untuk Meningkatkan Higher Order Thinking Skills (HOTS) dan Kemampuan Multipel Representasi Peserta Didik pada Materi Pokok Laju Reaksi - Sulfiani, Ridha; Muharram, Muharram; Ramlawati, Ramlawati (Program Pasca Sarjana UNM, 2023)
This development research aims to produce valid, practical and effective SiMaYang Type 2-based learning tools to improve Higher Order Thinking Skills (HOTS) and multiple representation abilities in reaction rate materials. The development model used in this study refers to the ADDIE development model developed by Robert Marie Branch (2009) covering 5 stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation . The tools developed in this research are Learning Implementation Plans (RPP), Student Worksheets (LKPD), modules, HOTS assessment instruments, and multiple representation ability instruments. The quality test phase of the SiMaYang Type 2-based learning device and the supporting instruments that will be used in the research is carried out through a validity test given to two validators. A limited trial of the use of SiMaYang Type 2-based learning tools was carried out on 15 class XII IPA students. Field trials were carried out on 56 students of class XI IPA. The results showed that the SiMaYang Type 2-based learning device developed met the product quality, namely: 1) the validity included: (a) lesson plans with a value of 3.48 (valid), (b) LKPD with a value of 3.58 (very valid) , (c) module with a value of 3.40 (valid), and (d) HOTS assessment instrument with a value of 0.77 (valid); 2) practicality includes: (a) the implementation of learning tools with a score of 1.80 in the fully implemented category, (b) teacher responses to learning tools with a value of 93.42% in the very practical category, (c) student responses 80.75% meet the very positive category; 3) effectiveness includes: (a) the ability of teachers to manage learning with a value of 3.38 is in the good category, (b) the ability of multiple representations of students with a value of 3.01 in the high category, (c) student activities of 76.22 % in good category, and (4) HOTS assessment with a pretest average of 14.30% in the low category and an average posttest of 78.01% in the medium category and the N-gain result of 0.76 in the high category. Thus, the results of the study indicate that the SiMaYang Type 2 learning model-based learning device has valid, practical and effective qualities.